2018
DOI: 10.1590/1678-992x-2016-0144
|View full text |Cite
|
Sign up to set email alerts
|

A hydropedological approach to a mountainous Clayey Humic Dystrudept in the Mantiqueira Range, southeastern Brazil

Abstract: ABSTRACT:The Mantiqueira Range region is one of the most important headwaters in southeastern Brazil. In this context, the relationship between pedology and hydrology has been debated and analyzed in recent years, contributing to the creation of a multidisciplinary science call hydropedology. Therefore, the aim of this study was to evaluate the hydropedological properties of a mountainous Clayey Humic Dystrudept in the Mantiqueira Range region, in the state of Minas Gerais, Brazil, comparing two land-uses, nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…The Grande River basin is located in southeastern Brazil and the Tropical Atlantic Forest in its headwater region (Mantiqueira Range), should be highlighted as one of the most important biodiversity hotspot of the world [1] [2]. In this basin, the annual variability of precipitation and temperature can be critical for human water consumption, irrigation, and hydropower generation [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…The Grande River basin is located in southeastern Brazil and the Tropical Atlantic Forest in its headwater region (Mantiqueira Range), should be highlighted as one of the most important biodiversity hotspot of the world [1] [2]. In this basin, the annual variability of precipitation and temperature can be critical for human water consumption, irrigation, and hydropower generation [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these results, we can state that there is an intrinsic relationship between land-use and hydrological flow indicators of the watersheds. These results are linked to the influence of the native forest, highlighting the interaction between interception and the direct impact of rainfall on the soil surface, and the saturated soil hydraulic conductivity (Pinto et al, 2018). Mello et al (2019) evaluating the intrinsic relationship between hydrology, soil, and forest in a tropical montane cloud forest (TMCF) inside Lavrinha watershed observed that baseflow was the main hydrological element in this site.…”
Section: Relationship Between Hydrological Indicators and Land-uses Imentioning
confidence: 91%
“…It is possible to observe a greater both precipitation and runoff in Lavrinha watershed (Figure 7), since this watershed is located in the south part of the UGRB, in the Mantiqueira Range (mountainous and strong undulated relief) (Figue 1). This part of the UGRB region is very susceptible to water erosion, which demands special concerns related to land-use and management (Pinto et al, 2018). Because of this, a better understanding of the relationships between hydrological indicators and land-use are necessary to better and more successful decision making for soil-water conservation and management targeting.…”
Section: Relationship Between Hydrological Indicators and Land-uses Imentioning
confidence: 99%
“…Concerning its hydrographic bases, the state of Minas Gerais has among its principal rivers: The Doce River, which rises between the slopes of the Mantiqueira and Espinhaço ranges [17] and flows into the Atlantic Ocean [18], in the Brazilian state of Espirito Santo; The Grande River, whose source is in the Serra da Mantiqueira [19], in the municipality of Bocaina de Minas until reaching the Paranaíba River, thus forming the Paraná River in the state of São Paulo; The Paranaíba River, which is born in the Wood of the Cord, in Paranaíba, and has approximately 1070 km of extension; and São Francisco River, which rises in the Serra da Canastra, cutting through the state of Bahia and passing through northeastern states like Pernambuco, Sergipe and Alagoas until it empties into the ocean, and itswater are essential for tourism, leisure, irrigation, and transportation in several cities, especially in northern Minas Gerais [20].…”
Section: Minas Gerais Statementioning
confidence: 99%